Pembelajaran Shorof menggunakan Buku Al-Maqsud dengan Metode Istiqraiyyah - Rohayati, Enok; Wasilah, Wasilah; Rahmadewi, Sintya (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2024)
This research is motivated by shorof learning which is still difficult to understand because it still uses general methods such as the lecture method, In the process of learning shorof there are still many students who have not been able to change the form properly and correctly. The existence of the Al-Maqsud Book and the istiqraiyyah method aims to make it easier for students to learn and understand students about shorof and shape change. The purpose of this study is to find out the learning of shorof before using the book Al-Maqsud with the istiqraiyyah method, to find out the learning of shorof after using the book Al-Maqsud with the istiqraiyyah method, and to find out the effectiveness of this research is a type of qualitative and quantitative research (Mixed Methods). With the Sequential Exploratory model, the first step is using qualitative data and then using quantitative data. This research data was obtained from observation, interviews, documentation, and tests. Based on the results of research obtained from the pre-test with an average student score of 49.33 and on the post-test 87.83. Based on the analysis of the T (Paired) test, a sig (2-tailed) value of 0.000<0.005 is obtained, which means that it can be concluded that Ha is accepted and Ho is rejected. So, it can be said that there is effectiveness after using the book Al-Maqsud with the istiqraiyyah method.